Epstein-Barr virus association with Hodgkin´s Lymphoma: A literature review (Research, Society and Development, 2022)
The management of Hodgkin's lymphoma has been a major challenge in recent decades, given its heterogeneity from the histopathological point of view and the range of changes at the cellular level that it causes. Many studies and researches are carried out with the objective of elucidating the association between the Epstein Barr virus and the respective pathology, in prognostic and clinical terms. The atypical neoplasm Hodgkin's Lymphoma, which was once confused even with other diseases, such as tuberculosis, since the cell that characterizes it, called Reed-Sternberg, transformed B cell, makes up the minority (1-5%) in the tumor population. The work had its methodology based on bibliographic research, considering renowned authors and scientific works, supported by theoretical foundation and with wide acceptance in the academic environment. Although the correlation of the Epstein Barr virus (EBV) in cancer cells is unquestionable, especially in patients who had infectious mononucleosis in childhood or youth, there is no certainty in the scientific world about the prognostic correlation of this association. Even so, studies demonstrate worsening prognosis and survival in those patients in whose cells EBV genes are expressed. In addition, possible investigations regarding the classification of the disease, risk factors, clinical manifestations, diagnosis, staging, favorable or unfavorable factors and treatment of the disease will be evaluated, in addition to some mechanisms that involve the pathogenesis of cancer and EBV. The methodology in this case study consists of a fundamental, descriptive, explanatory, bibliographic, longitudinal and retrospective research.